Are unmet needs driving requests for Medical Assistance in Dying (MAiD)? A qualitative study of Canadian MAiD providers. Issue 2 (7th February 2023) - Wiebe, Ellen R.; Kelly, Michaela; Spiegel, Laura; Menard, Jean-Frederic; Hawse, Emily; Dickinson, Rebecca
Abstract: In this study, 20 medical assistance in dying (MAiD) providers were interviewed about their experience when assessing patients with unmet needs, including medical, financial or social needs. Collectively they had experience with over 3700 MAiD assessments and found that unmet needs were rare. In the cases where patients had unmet needs, these were usually related to loneliness and poverty. This led to the ethical dilemma of providers deciding to honor their wishes for MAiD, knowing that some of their suffering was due to society's failure to provide for them.